Passport to the heart : reflections on Canada Caribbean relations - Carmichael, Trevor A. (Ian Randle Pub. KingstonJM, 2001)
Focuses on the theme of collaboration and cooperation. Examines areas such as the economy, polity, culture, law and the mobility of labour.